Effects of perioperative oxygen concentration on oxidative stress in adult surgical patients: a systematic review. (March 2021) - Oldman, Alexander H.; Martin, Daniel S.; Feelisch, Martin; Grocott, Michael P.W.; Cumpstey, Andrew F.
Abstract: Background: The fraction of inspired oxygen (FiO2 ) administered during general anaesthesia varies widely despite international recommendations to administer FiO2 0.8 to all anaesthetised patients to reduce surgical site infections (SSIs). Anaesthetists remain concerned that high FiO2 administration intraoperatively may increase harm, possibly through increased oxidative damage and inflammation, resulting in more complications and worse outcomes. In previous systematic reviews associations between FiO2 and SSIs have been inconsistent, but none have examined how FiO2 affects perioperative oxidative stress. We aimed to address this uncertainty by reviewing the available literature. Methods: EMBASE, MEDLINE, and Cochrane databases were searched from inception to March 9, 2020 for RCTs comparing higher with lower perioperative FiO2 and quantifying oxidative stress in adults undergoing noncardiac surgery. Candidate studies were independently screened by two reviewers and references hand-searched. Methodological quality was assessed using the Cochrane Collaboration Risk of Bias tool. Results: From 19 438 initial results, seven trials ( n =422) were included. Four studies reported markers of oxidative stress during Caesarean section ( n =328) and three reported oxidative stress during elective colon surgery ( n =94). Risk of bias was low (four studies) to moderate (three studies). Pooled results suggested high FiO2 was associated with greater malondialdehyde, protein-carbonyl concentrations and reduced xanthine oxidase concentrations, together with reduced antioxidant markers such as superoxide dismutase and total sulfhydryl levels although total antioxidant status was unchanged. Conclusions: Higher FiO2 may be associated with elevated oxidative stress during surgery. However, limited studies have specifically reported biomarkers of oxidation. Given the current clinical controversy concerning perioperative oxygen therapy, further research is urgently needed in this area.